The shavenoid gene of Drosophila encodes a novel actin cytoskeleton interacting protein that promotes wing hair morphogenesis. - Ren, N.; He, B.; Stone, D.; Kirakodu, S.; Adler, P.N. (Genetics, 2006)
The simple cellular composition and array of distally pointing hairs has made the Drosophila wing a favored system for studying planar polarity and the coordination of cellular- and tissue-level morphogenesis. The developing hairs are filled with F-actin and microtubules and the activity of these cytoskeletons is important for hair morphogenesis. On the basis of mutant phenotypes several genes have been identified as playing a key role in stimulating hair formation. Mutations in shavenoid (sha) (also known as kojak) result in a delay in hair morphogenesis and in some cells forming no hair and others several small hairs. We report here the molecular identification and characterization of the sha gene and protein. sha encodes a large novel protein that has homologs in other insects, but not in more distantly related organisms. The Sha protein accumulated in growing hairs and bristles in a pattern that suggested that it could directly interact with the actin cytoskeleton. Consistent with this mechanism of action we found that Sha and actin co-immunoprecipitated from wing disc cells. The morphogenesis of the hair involves temporal control by sha and spatial control by the genes of the frizzled planar polarity pathway. We found a strong genetic interaction between mutations in these genes consistent with their having a close but parallel functional relationship.